20 years of suburbanisation of the population - Schönert, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Every year the major German cities are losing inhabitants through the suburbanisation of their urban fringe. The study of seven major cities reveals an annual negative migration balance of about 0.5% of the total population between 1981 and 2000. Thus approximately 10% of the urban population migrated to the surrounding countryside in 20 years. Suburbanisation is an essential reason for the ratio of population-related housing completions, in which the inner city brings considerably fewer dwellings onto the market — with a ratio of 1∶1.7 — in comparison with the urban fringe. The building type of so-called “single-family” and “two-family” houses plays a special role in the process of suburbanisation. The study illustrates the greater attractiveness of the urban fringe and the scarce availability of building sites in the inner cities for the construction of single-family and two-family houses: as a result, the population-related housing completions in urban fringe areas are four to five times higher than in the city centre.